Prevalence of Methotrexate Intolerance in Patients with Rheumatoid Arthritis, Psoriatic Arthritis and Juvenile Idiopathic Arthritis: Methotrexate Intolerance with Rheumatoid Arthritis and Juvenile Idiopathic Arthritis - Ali, Usman; Ali, Amjad; Din, Imad Ud; Ahmad, Hajra; Imran, Muhammad; Zeb, Alam (Pakistan Journal of Health Sciences, 2025)
Methotrexate intolerance is frequently encountered, however, seldom studied scientifically in a low-resource setting. Hence, the study was planned to look for the areas for possible early interventions that may assist in decreasing or preventing intolerance, and its early identification may impact treatment, leading to timely changes in medication that may promote patient compliance and better control of the disease. Objectives: To determine the prevalence of methotrexate intolerance in patients with rheumatoid arthritis, psoriatic arthritis and juvenile idiopathic arthritis. Methods: This descriptive comparative study was carried out at the Department of Rheumatology, Khyber Teaching Hospital, Peshawar, during the period 12th February 2025 to 31st May 2025. Male and female patients aged 10 to 70 years diagnosed with rheumatoid arthritis, psoriatic arthritis and juvenile rheumatoid arthritis were enrolled and evaluated for methotrexate intolerance using the MISS questionnaire, taking a score ≥6 as a cut-off for the presence of intolerance. Results: Mean age was 38.85 ± 17.31 years, and the majority of participants had an age of more than 40 years (n=81, 53.6%), while 91 patients (60.3%) were male. Rheumatoid arthritis was the most common clinical diagnosis (n=91, 60.3%). Overall, methotrexate intolerance was observed in 58 (38.4%) patients. Methotrexate intolerance was most common in rheumatoid arthritis patients (n=38, 41.8%) (p-value=0.323). Conclusions: Though methotrexate intolerance is fairly common among patients with rheumatic disorders, no statistically significant association was observed between intolerance and background disease or baseline parameters such as route of administration.